2011
DOI: 10.2298/avb1103193k
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Listeria spp. in fish samples, fish products and sea products

Abstract: Listeria monocytogenes is a bacterium that is pathogenic for man and for most animal species. Listeriosis is a generalized infection that starts after ingestion of the causative agent L. monocytogenes (Finlay, 2001). Food that is not properly thermically processed, long storage of such food, food that is produced in inadequate hygienic food plants, as well as cooked-cooled ready to eat food (RTE) is the ideal medium for listeria multiplication. High risk food originated from fish, fish products and sea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…in raw fish and shrimp samples, recently reviewed in Jami, Ghanbari, Zunabovic, Domig, and Kneifel (2014). In these reports, the rate of L. monocytogenes contamination in raw fish and shrimp samples ranged from 43.3% (Chen et al, 2010) to 0% (Kuzmanovi c et al, 2011;Minami et al, 2010;Wang, Chern, Li, Yan, & Hsieh, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…in raw fish and shrimp samples, recently reviewed in Jami, Ghanbari, Zunabovic, Domig, and Kneifel (2014). In these reports, the rate of L. monocytogenes contamination in raw fish and shrimp samples ranged from 43.3% (Chen et al, 2010) to 0% (Kuzmanovi c et al, 2011;Minami et al, 2010;Wang, Chern, Li, Yan, & Hsieh, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…were also identified in 12% of 470 samples of fresh, frozen, salted, smoked and thermally processed fish and seafood. In this investigation, L. monocytogenes was present in 2% of the samples [21].…”
Section: Listeria Monocytogenesmentioning
confidence: 54%
“…Frozen fish are prone to contaminated by Listeria spp. (Reij et al, 2004;Jelena et al, 2011). Previously several studies showed that some thermostable enterotoxin of Staphylococcus aureus and Escherichia coli would not destroy completely even after cooking of seafood or if the food cooked properly, due to improper handling recontamination can take place and consumption of this type of food causes severe food poisoning (Ayulo et al, 1994;Vieira et al, 2001;Omeo et al, 2005;Simon and Sanjeev, 2007;Beleneva, 2011;Tango et al, 2015).…”
Section: Introductionmentioning
confidence: 99%